What is the standard form of y=(-2x-15)(3x-1)?

Rinoslirl9h1

Rinoslirl9h1

Answered

2022-02-01

What is the standard form of y=(-2x-15)(3x-1)?

Answer & Explanation

anthonystb5

anthonystb5

Expert

2022-02-02Added 11 answers

Explanation:
To transform this equation to standard form you can multiply these two terms by multiplying each individual term in the left parenthesis by each individual term in the right parenthesis.
y=(-2x-15)(3x-1) becomes:
y=(2x×3x)+(2x×1)(15×3x)+(15×1)
y=6x2+2x45x+15
We can now combine like terms:
y=6x2+(245)x+15
y=6x2+(43)x+15
y=6x243x+15

Do you have a similar question?

Recalculate according to your conditions!

Ask your question.
Get your answer.

Let our experts help you. Answer in as fast as 15 minutes.

Didn't find what you were looking for?